Fourier-based spatial mapping of oscillatory phenomena in fungi. - Fricker, M; Tlalka, M; Bebber, D; Takagi, S; Tagaki, S; Watkinson, S; Darrah, P (2007)
Microorganisms display a range of oscillatory phenomena that operate over different temporal scales. Fourier analysis provides a compact description of such oscillations in terms of their frequency, magnitude and phase. However, in the majority of studies there is no explicit consideration of the spatial organisation of the oscillation. Here we describe procedures and a software package to map oscillatory phenomena in microorganisms in both the time and frequency domains. Key parameters of interest, such as frequency, phase or magnitude of the oscillations, are presented as pseudo-colour coded maps. This maintains the spatial information in the image and greatly facilitates understanding of potentially complex propagating waves or development of oscillatory domains with distinct behaviour. We illustrate the utility of this system with reference to spatial analysis of the pulsatile component to amino acid transport in mycelial systems of Phanerochaete velutina and Coniophora puteana, and actin-myosin based contractions in Physarum polycephalum.